ANALISIS DENGAN METODE ETHNONURSING LEININGER PREVALENSI KUSTA: SOSIAL, BUDAYA DAN PERAN TENAGA KESEHATAN - Swastika, I Ketut; Bahari, Bahari; Payasan, Lalu Guntur; Abimulyani, Yumi; Susanto, Wibowo Hanafi Ari; Purba, Lilys Irianty Natalia (Media Penelitian dan Pengembangan Kesehatan, 2024)
Leprosy has not been eliminated in six provinces in Indonesia, one of which is Papua. Mappi Regency, Papua, contributed one thousand cases of leprosy in the last five years and 100 active cases in 2020. The high leprosy prevalence in Mappi Regency is still a mystery of the main cause. It is necessary to explore the causes of the high prevalence of leprosy in the region. The study aimed to explore socio-cultural factors and the role of health workers on the prevalence of leprosy in Mappi Regency, Papua, Indonesia. The study method was Qualitative ethnonursing by purposive sampling. This research was conducted in Mappi Regency. Data saturation was obtained from fourteen informants: four leprosy patients, four leprosy patients' families, three health workers, and three stakeholders in Primary Health Center Kepi, Kota 2, Senggo, and Health Office Mappi. Data retrieval and processing with Leininger's Ethnonursing analysis was assisted by Atlas.ti application. The study result showed there were seven emerging themes, including social and cultural: leprosy is considered like a common disease, changes in economic situation, affordability and geographical conditions, leprosy care by patients, families, and communities, suboptimal practices of health workers, limited role of government, budget, and logistics, and expectations for handling leprosy cases. The study concluded that social and cultural factors and the role of health workers contribute to the prevalence of leprosy in Mappi District, Papua, Indonesia. Strengthening the role of families, communities, health workers, and government policies is needed to support the recovery of leprosy patients and reduce the prevalence of leprosy.